Clinical effectiveness of efinaconazole 10% solution for treatment of onychomycosis with longitudinal spikes. Issue 10 (1st July 2021) - Watanabe, Shinichi; Iozumi, Ken; Abe, Masatoshi; Ito, Yoshiko; Uesugi, Takashi; Onoduka, Takashi; Kato, Ichiro; Kato, Fumihiro; Kodama, Kazuo; Takahashi, Hidetoshi; Takeda, Osamu; Tomizawa, Koki; et al.
Abstract: Onychomycosis with longitudinal spikes in the nail plate has been reported to be refractory to oral drugs as with dermatophytoma. We evaluated the efficacy of 10% efinaconazole solution in the treatment of onychomycosis with longitudinal spikes. Of the 223 subjects who were enrolled in a previous study, a post‐hoc analysis of 82 subjects with longitudinal spikes was performed in this study. The opacity ratio of longitudinal spikes was decreased over time from 8.1 to 0.9 at the final assessment. In addition, the longitudinal spike disappearance rate increased early after the application to 81.7% at the final assessment. Therefore, 10% efinaconazole solution can be a first‐line drug for longitudinal spikes, which have been regarded as refractory to oral drugs.